Examining Changes in GDP on the Demand for Road Freight Transport. (2017) - Varjan, Pavol; Rovňaníková, Dominika; Gnap, Jozef
Abstract: The paper deals with the analysis of long-term development of GDP, while it is per 1 capita in Slovakia and neighboring countries. This development will be further compared with the economies of developed countries. This paper also parse the vehicle fleet of road transport and examines the burden on the road network. This is based on statistical data from the Slovak Road Administration and information from the toll system since 2009. The paper also examine the load of roads in the factory Kia Motors Slovakia by road freight transport. The output of paper are recommendations for the development of transport infrastructure, road and rail transport in terms of sustainable development.